Single-walled carbon nanotubes: differential genotoxic potential associated with physico-chemical properties. Issue 2 (March 2013) - Manshian, Bella B.; Jenkins, Gareth JS.; Williams, Paul M.; Wright, Chris; Barron, Andrew R.; Brown, Andrew P.; Hondow, Nicole; Dunstan, Peter R.; Rickman, Rob; Brady, Ken; Doak, Shareen H.
Abstract Single-walled carbon nanotubes (SWCNTs) have recently attracted great attention because of their fibrous structure and high aspect ratio. Here the genotoxic potential of 400–800 nm, 1–3 μm and 5–30 μm SWCNT with respect to their geometry and surface characteristics was studied. Following thorough physico-chemical characterisation, human bronchial epithelial (BEAS−2B) and lymphoblastoid (MCL-5) cells were treated with SWCNT for 24 or 48 h. This showed significant increases in micronucleus frequency in a time- and dose-dependent manner in both cell types in the absence of cytotoxicity. Over the same dose range, only 1–3 μm SWCNT gave rise to significant increases in hprt point mutations at doses ≥25 μg/ml. Cellular 2, 7-dichlorodihydrofluoresceindiacetate (DCFH-DA) fluorescence assay and RT-PCR for oxidative pathway gene profiling revealed a possible oxidative mechanism for the genotoxicity observed in the 1–3 μm SWCNT. Consequently, this study has demonstrated that SWCNT genotoxicity is dependent on its secondary structure under experimental conditions and oxidative stress alone cannot account for the observed damage.